Makna Pengkhususan pada QS. al-Baqarah Ayat 256: Analisis Semiotika Charles Sanders Peirce PeircePeirce Peirce - Yuviandze Bafri Zulliandi (Jurnal Semiotika Quran, 2024)
This document analyzes the meaning of specialization in QS. al-Baqarah verse 256 on religious freedom using the semiotic framework of Charles Sanders Peirce. The author explains that Peirce's epistemology is built on four pillars: fallicanism, positive social encouragement, idealistic objectivity, and pragmatism. Peirce also developed the concepts of trichotomy and tripartity in analytic logic, which showed the existence of a set of three interrelated meanings in interpretation. In QS. al-Baqarah verse 256, there is a debate about the concept of religious freedom. Some scholars argue that there is no absolute freedom to change religions. The author of the article tries to analyze the specialization in the verse using 10 signs of Peirce's triadic sign, namely: rheme-icon-qualisign, rheme-icon-sinsign, rheme-index-sinsign, and so on. The analysis of the specialized meaning in verse 256 of QS. al-Baqarah using the semiotic approach of Charles Sanders Peirce reveals ambiguity in the interpretation and application of this verse. The verse emphasizes the absence  of  compulsion in religion  and the clear  distinction between the right path and the wrong path. The concept of religious freedom is examined through  Peirce's triadic approach, which helps to understand the complexity in the inter-pretation of religion.